Peran PGMI dalam Mewujudkan Guru Madrasah Ibtidaiyah yang Berdaya Saing Global - Hamid, Ahmad Dhani (Maliki Interdisciplinary Journal, 2026)
The Islamic Elementary School Teacher Education Program (PGMI) plays a crucial role in preparing professional, competitive, and globally relevant teachers for Islamic elementary schools. This article aims to describe PGMI’s role in shaping globally competitive teachers by strengthening pedagogical, professional, social, and spiritual competencies. Using a literature review approach, this study analyzes scholarly works related to teacher education transformation in the Independent Curriculum era, digital technology integration, and the challenges of educational globalization. The findings indicate that PGMI must develop adaptive curricula, enhance digital literacy skills, strengthen character education, and foster international collaboration. This aligns with the vision of madrasah as an Islamic educational institution that produces globally competent teachers while maintaining Islamic identity.